178k views
4 votes
Dividing Rational Expressions

Dividing Rational Expressions-example-1

1 Answer

4 votes

Answer:


(6)/((x + 2))

Explanation:


(2x + 2)/(x + 2) / \frac{4 {x}^(2) +8 x + 4}{12x + 12} \\ \\ = (2(x + 1))/(x + 2) / \frac{4( {x}^(2) + 2x + 1) }{12(x + 1)} \\ \\ = (2(x + 1))/(x + 2) / (( x + 1)^(2) )/(3(x + 1)) \\ \\ = (2(x + 1))/(x + 2) * \frac{3(x + 1)}{ {(x + 1)}^(2) } \\ \\ = \frac{6 {(x + 1)}^(2) }{(x + 2) {(x + 1)}^(2) } \\ \\ = (6)/((x + 2))

User Matcartmill
by
5.5k points